Morte, memória e família: a prática e os atores testamentários em Mariana, 1748-1848 - Karina Aparecida de Lourdes Ferreira (2019)
The present study analyzes the funeral rites recommended in the wills of residents of the city of Mariana between the second half of the Eighteenth Century and the first of the next Century. The guiding assumption is that the then-current idea of a socially desirable death supposed the involvement of the individual in social ties of different nature and mobilized a series of instruments in order to guarantee duration to a certain content of memory. In other words, a good death was associated with the intercession of the living and the ability to be remembered among them. From this point of view, this work not only investigates preferred funeral practices and their adjacent meanings, but also the different groups involved in the execution of posthumous care and the mnemonic expectations contained in these measures. The different social frameworks expressed in the documentation were taken into account, through which the mutual conditioning between religious and family dimension was observed, and the increasing projection of the latter in the advance of the Nineteenth Century.